Information technology enhances students' academic performance: a case Of University Of Ilorin - Ahlan, Abdul Rahman; Atanda, Balogun Naeem; Yahaya, Isah Shehu; Shehu, Yahaya Isah (Sakarya University, Turkey, 2014)
This study aims to investigate the impact of Computer Based Test in enhancing students’ academic performance, its acceptance and how it can be improved upon. In addition, the study also tries to access the computer ownership and its impact to students’ performance in Computer Based Testing. The study use questionnaire-based survey to gather responses from the students in order to understand if technology usage has impact on student’s academic performance, and their acceptance of technology to conduct examination. Findings of this study shows significant relationship between computer ownership and the use of technology for examination, and technology with students’ academic performance. The findings should assist the learning institution to improve the implementation of e-learning in order for the students’ to have best results and facilitate its technical know-how so that it will gain acceptance by all the students especially the at-risk students and the physically challenged. The research provides useful information for learning institution based on the students’ academic performance due to the recent development and implementation of Computer Based Testing.